Oral Health Status Among Schoolchildren: Does Partnership With School of Dentistry Make A Difference? - Sri Widiati (Fakultas Kedokteran Gigi, Universitas Gadjah Mada, 2011)
The purpose of this study was to evaluate whether the partnership between 26 primary schools with the Faculty of Dentistry, Universitas Gadjah Mada, during the past 12 years improved oral health status of the schoolchildren. A sample survey was carried out, involving 106 fifth and sixth graders from 9 schools which have been participating in the partnership and 90 schoolchildren from non-participating schools. They were examined by trained dental students. Oral health status was represented by OHI-S and DMF-t measurement. Knowledge and attitude of oral health were measured using structured questionnaires. The study indicated that the means of OHI-S and DMF-t among schoolchildren participating in the partnership were 0.11 and 0.01 lower respectively compared to those of their counterparts, although the differences were not significant statistically. The knowledge and attitude among schoolchildren in the partnership were 2.49, 4.18, and 3.86 higher, all were highly significant (p < 0.001). Path analyses showed that the partnership reduced OHI-S and DMF-t with an overall path coefficients – 0.086 and -0.076 respectively. Although knowledge was associated with DMF-t and attitude with OHI-S, there were other unmeasured variables which were more strongly associated with oral health status of the schoolchildren.